Analysis of Project Network Planning Using the Critical Path Method - Moh. Akhir; Koespiadi Koespiadi; F. R. Edy Santosa (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
In the development of the implementation of building construction projects, work is often delayed from the specified time, to overcome this, an implementation method is needed, one of which is using Network Planning with the Critical Path Method (CPM ). CPM is a basic method of planning and controlling a work system based on a network or network that can increase efficiency and effectiveness in allocating time and costs. The research method used is the primary research method, conducting observations or direct observations in the field and conducting face-to-face interviews on projects being implemented with a self-management system, carried out by the SMK Negeri 1 Bualemo school by forming a school construction team (P2S). The application of network planning with the CPM method in building construction can accelerate the project implementation schedule compared to the specified time and can increase the cost effectiveness of project implementation. The results of the study using CPM are known to be Critical Paths, namely Activities A – C – H – L – M – N – T – W – X – Y with the original project completion time of 175 days to 157 days, optimizing the time by 18 days, with the original Budget of Rp. 2,224,035. 000,- to Rp. 2,140,996,000 ,- cost optimization of Rp. 83,038,723.02.